Two new species of the genus Viscosia de Man, 1890 (Nematoda, Enoplea, Enoplida, Oncholaimidae) from the intertidal zone of the Yellow Sea, China - Lingyun Sun; Huimin Gu; Yong Huang (ZooKeys)
Two new species of Viscosia from the intertidal zone along the Yellow Sea are described and illustrated. Viscosia media sp. nov. is characterized by a heavily cuticularized and relatively shallow buccal cavity with stubby teeth; cephalic setae 7–8 µm long; amphidial fovea invisible; slender spicules almost straight, cephalated proximally and conical distally; and tail conical, straight in males and slightly bent ventrally in females. Viscosia sinica sp. nov. is characterized by a relatively large amphidial fovea, conico-cylindrical tail with swollen horseshoe-shaped tip, spicules slightly curved ventrally, and 10–12 setae surrounding the cloaca, each 3–4 µm long. The basic morphological data of males of 26 valid species in Viscosia with a body length of 1–2.9 mm are presented.